Economic evaluation of healthcare safety: which attributes of safety do healthcare professionals consider most important in resource allocation decisions?. Issue 5 (10th August 2010) - Steuten, L; Buxton, M
Abstract : Introduction: There is an increasing need to assess the value of safety improvements to society. Concerns exist, however, as to what extent standard health economic methods appropriately reflect this value because these methods do not typically incorporate the non-health or extra-consequentialist value of avoiding healthcare incidents, which may—for example, be associated with a decreased trust of patients and citizens in healthcare systems and providers. Objectives: (1) To identify health and non-health attributes of safety from the literature and (2) to prioritise those that are considered most important by healthcare decision-makers and could be included in a subsequent conjoint analysis to determining the relative value of safety interventions and the willingness to pay of decision-makers. Methods: A literature review and 25 semistructured interviews have been conducted with healthcare decision-makers experienced in safety management, considering a general healthcare, Methicillin-resistant Staphylococcus aureus (MRSA) and sharps injuries context. Results: The literature review showed that in addition to likelihood of an incident and its direct medical and cost consequences, factors such as preventability, dread, controllability and trust in safety devices or systems affect the value of safety and decision-makers' willingness to pay. The interview results consistently indicated that "preventability of healthcare incidents", "health consequences", "financial consequences" and "trust in safety systems/devices" are the most important attributes across all contexts. In addition, context-specific attributes were identified. Conclusion: A set of four common and two context-specific attributes, including health and non-health aspects of safety, was identified. The next step is to attaching appropriate levels to these attributes and to incorporate them into a series of case studies among various groups of decision-makers, healthcare professionals, patient groups and the general public.